Correlation of Standard Operating Procedures and Work Environment to Employee Work Discipline of PT Ghania Creative Indonesia with Work Motivation as an Intervening Variable - Melyng, Navisa Tan; Widodo, Slamet; Setiawan, Nashrudin (Journal of Business Management and Economic Development, 2024)
This study aims to test and find out how the correlation of the application of standard operating procedures and work environment conditions to the level of work discipline of PT Ghania Creative Indonesia employees with work motivation as an intervening variable. This research uses quantitative research methods, with a correlation analytic approach. The population of this study amounted to 40 people and the sampling technique used total sampling technique, so the number of research samples became 40 people. This research data collection method uses a questionnaire / questionnaire method. The results showed that each independent variable partially had a direct effect on the level of employee discipline. Simultaneously, the application of the SOP and the work environment has a direct effect on the level of employee work discipline with a value of Fcount (5.527) > Ftable (2.87) with a significance level of 0.000. Furthermore, it has an R square value of 0.647 or 64.7% which means that as far as 64.7% there is a significant and direct influence of the application of SOPs and the work environment on employee work discipline together, while the other 35.3% are variables not examined in this study.